Validation and Optimal Cut-Off Scores of the Bahasa Malaysia Version of the Montreal cognitive assessment (MoCA-BM) for mild cognitive impairment among community dwelling older adults in Malaysia - Normah Che Din; Suzana Shahar; Baitil Husna Zulkifli; Rosdinom Razali; Chyn, Ai Vyrn; Azhadi Omar (Penerbit Universiti Kebangsaan Malaysia, 2016)
The goal of this study was to examine the reliability and validity of the Bahasa Malaysia version of the Montreal cognitive assessment (MoCA-BM) and to determine its optimal cut-off score among older adults with mild cognitive impairment (MCI), after adjustments for age, gender, levels of education, physical functioning and depressive symptoms. A total of 2237 community dwelling older adults aged 60 years and above were randomly selected for the study, excluding those with MMSE score below 14. Instruments administered were the MoCA-BM, the Malay Mini-Mental State Examination (MMMSE), the Rey Auditory Verbal Learning Test (RAVLT), the Digit Span and the Digit Symbol subtests of the Wechsler Adult Intelligence Scale (WAIS), activities of daily living (ADL) and the Geriatric Depression Scale (GDS). MCI were determined using the Petersen’s 2014 criteria as the gold standard. SPSS version 22 was used for reliability and validity analysis and optimal cut-off score detection. Cronbach’s α of the MoCA-BM was 0.691 and concurrent validity was high between MoCA-BM and MMMSE scores (r=0.741). Optimal cut-off point for MoCA-BM to detect MCI among older adults in Malaysia was 17/18, with sensitivity of 68.2% and specificity of 61.3%. Using this cut-off, 38.9% of participants were detected to be at risk of MCI. In conclusion, MoCA-BM is a reliable and valid screening instrument for MCI among Malaysian elderly community. The newly derived optimal cut-off for MCI is much lower than the original MoCA with modest ability to discriminate between normal and MCI older adults in the community.